DOI: 10.14264/uql.2016.301
|View full text |Cite
|
Sign up to set email alerts
|

Beach recovery and studies in accretive sediment transport

Abstract: Erosion has been a focal point in sediment transport research while sediment accretion has been neglected until recent times. This thesis addresses some components of accretive sediment transport through modelling and new experimental measurements.The existing Grab and Dump model (Nielsen, 1988), a simple sediment transport model over rippled beds, is generalised to reflect a wider range of flow conditions, including acceleration skewed flows, boundary layer streaming, sheet flows, and cases with superimposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 103 publications
(289 reference statements)
1
4
0
Order By: Relevance
“…The results were consistent with the threshold value of 𝐴𝐴 𝐴𝐴𝑚𝑚𝑚𝑚𝑚𝑚𝑑𝑑50𝜔𝜔∕𝑤𝑤𝑠𝑠 = 0.038 (Dohmen-Janssen et al, 2002). Lower net transport rate of WS-M under waves with high velocity skewness is also consistent with the previous measurement of coarse (d 50 = 0.465 mm) and fine (d 50 = 0.125 mm) sand under velocity skewed flows (analyzed by Shimamoto (2016)). Interestingly, for the BM consisting of only 30% coarse fraction, the trend of the net transport rate as a function of <U 3 > is similar to that of WS-C.…”
Section: Net Sediment Transport Ratessupporting
confidence: 92%
“…The results were consistent with the threshold value of 𝐴𝐴 𝐴𝐴𝑚𝑚𝑚𝑚𝑚𝑚𝑑𝑑50𝜔𝜔∕𝑤𝑤𝑠𝑠 = 0.038 (Dohmen-Janssen et al, 2002). Lower net transport rate of WS-M under waves with high velocity skewness is also consistent with the previous measurement of coarse (d 50 = 0.465 mm) and fine (d 50 = 0.125 mm) sand under velocity skewed flows (analyzed by Shimamoto (2016)). Interestingly, for the BM consisting of only 30% coarse fraction, the trend of the net transport rate as a function of <U 3 > is similar to that of WS-C.…”
Section: Net Sediment Transport Ratessupporting
confidence: 92%
“…The Gourlay number or dimensionless fall velocity, Ω, (Gourlay, 1968 and has been repeatedly demonstrated to be a useful parameter for predicting beach states and profile response (e.g. Nayak, 1970;Hattori and Kawamatta, 1980;Wright and Short, 1985;Shimamoto, 2016, Baldock et al, 2017 which has the form:…”
Section: Static Equilibrium Profilesmentioning
confidence: 99%
“…Some consider equilibrium to be achieved in just a couple of hours (Nayak, 1970;Srisuwan et al, 2014), while others reported several (Dalrymple and Thompson, 1974;Shimamoto, 2016),…”
Section: Static Equilibrium Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this present study, only the coarse sand case is studied (coarse sand corresponding to a median grain diameter greater than 0.400 mm). Shimamoto (2016) shows the influence of sand grain size on transport behavior in the reference frame of different rippled beds and various hydrodynamic conditions, mostly with Figures 3–1 (page 49 from Shimanoto, 2016). This study shows that offshore transport occurs for high velocity skewness in the fine sand case, whereas offshore transport occurs for low asymmetry in the coarse sand case.…”
Section: Introductionmentioning
confidence: 98%